Analisis Kesalahan Berbahasa pada Teks Laporan Hasil Observasi Siswa Kelas VIII SMP 2 Rajadesa (International Forum of Researchers and Lecturers, 2024)
This study aims to describe: (1) types of errors in the use of Indonesian language which include errors in spelling, word choice, sentence structure, and paragraph structure; (2) factors causing errors in observation reports of grade VIII students at SMPN 6 Rajadesa; and (3) efforts made to overcome these language errors. This study uses a qualitative descriptive method with a content analysis approach to samples in the form of observation reports from 3 grade VIII students of SMPN 2 Rajadesa. The results of the study show that: First, the forms of language errors found include errors in spelling, choice of diction, sentence structure, and paragraph structure. Second, factors causing language errors in the report include students' lack of understanding of language rules, inaccuracy when writing, low motivation in writing, and limited student vocabulary. Third, efforts made to correct language errors in this observation report include the application of writing learning with a process approach, increasing understanding of language rules through reading activities, and increasing writing practice for students.